User Satisfaction Analysis of Pln Mobile Application at Jabodetabek - Tya Nur Aini (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The ease of use and usefulness of an application are pivotal factors in determining user satisfaction. The objective of this study is to analyse the level of user satisfaction with the PLN Mobile application in the Jabodetabek area. The data were collected via an online questionnaire distributed through various platforms, including WhatsApp, Instagram, and Facebook. The study population consisted of individuals who had utilized the PLN Mobile application for a minimum of three months and were at least 17 years of age. A sample of 116 respondents was obtained using Slovin’s formula. The data was analysed using the statistical software package SPSS (Statistical Package for the Social Sciences) version 27, which enabled the researcher to perform a range of descriptive, validity, reliability, mean, standard deviation and T-tests. The results of the study, based on the mean tests, indicated that users were satisfied with the PLN Mobile application in terms of ease of use and satisfaction, information management system, and usefulness, all of which significantly contributed to overall user satisfaction. Based on these findings, the marketing implications of this study suggest that application developers should enhance user satisfaction by improving reliability features and customer service to provide better user experiences.